Design of a Teleoperation Haptic Control System with Network Delay Compensation Using Passivity Based Control and Observers - Anggara, Riswan (Cattleya Darmaya Fortuna, 2024)
This study proposes a robust bilateral haptic teleoperation control architecture against time-varying network delays by combining Passivity-Based Control (PBC), passivity observer–controller (PO/PC), energy tank, and passivated observers (disturbance/force observer and passivity-limited Kalman filter). The communication channel is modeled as a packet network with delay, jitter, and packet loss, while transparency and stability are maintained through scattering variables and passivity metric-based adaptive energy regulation. Validation is performed on three network scenarios (light–medium–heavy) through simulation/Hardware-in-the-Loop and WAN emulation tests. Results show that the complete scheme significantly decreases position RMSE and force RMSE compared to the PBC baseline, generally in the range of 25–40%, widens the Z-width by about 35–60%, and improves the MOS of haptic perception. Energy-based stability indicators show Max ΔE ≈ 0 and the tank energy remains positive, confirming the passivity and stability of input–output under delay/jitter/loss variations. Mechanistically, adaptive coupling between the PO/PC and the observer keeps the system stable when conditions deteriorate and restores transparency when conditions improve. These findings confirm the feasibility of a passivity-based approach for haptic teleoperation in real packet networks and open the development direction to multi-DOF, energy-based event-triggered communication, and large-scale user studies.